12x-7-3x=3-4x-10

Simple and best practice solution for 12x-7-3x=3-4x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-7-3x=3-4x-10 equation:



12x-7-3x=3-4x-10
We move all terms to the left:
12x-7-3x-(3-4x-10)=0
We add all the numbers together, and all the variables
12x-3x-(-4x-7)-7=0
We add all the numbers together, and all the variables
9x-(-4x-7)-7=0
We get rid of parentheses
9x+4x+7-7=0
We add all the numbers together, and all the variables
13x=0
x=0/13
x=0

See similar equations:

| 50•w=32 | | 3x-17=4x–2x–6 | | −9x−1=−8x+15. | | 3=a-1+a | | 4.3+10m=8.27 | | 48-x=48 | | -6.5(6y-3.5)=-19.5 | | -9=u/3+-6 | | 11(x+7)=5(6x-8)-6x | | 9k-(-3k-7)=15 | | (6x+20)+(2x+4)=0 | | 49=x−48 | | 0.07g-6.5=0.2g | | 2x+56=4x-14 | | 3x-12=6x+5 | | -5x20=100 | | 7p+5p-3p=21+9-10 | | 7a−3=13a+7 | | -4+33=2x+81 | | -6(h+7)+8=-19 | | (6+6x)=-22x+2 | | -26=-10+8k | | (5u+10)=5 | | 4≤x+2≤=8 | | -10n-35=0 | | 8n-(4n+5)=9 | | -3=x-1-3 | | 11+21=-4(6x-8) | | (4n+19)-(6(n-9))=0 | | 83=21+m | | 8(y+2)+2y=-34 | | 5(x-5)=4(x+8) |

Equations solver categories